2017
DOI: 10.1021/acssuschemeng.7b00092
|View full text |Cite
|
Sign up to set email alerts
|

Absorption Behavior of Acid Gases in Protic Ionic Liquid/Alkanolamine Binary Mixtures

Abstract: Herein, we studied the absorption of H 2 S and CO 2 by alkanolamine−protic ionic liquids binary mixtures based on 2-hydroxyethylammonium (MEA) or triethanolammonium cations and residues of 2hydroxy-5-sulfobenzoic acid or pyridine-3-carboxylic acid at various temperatures and partial gases pressures. It was found that absorbents based on the 2-hydroxyethylammonium cation, performed high absorption properties toward the H 2 S. The solubility of hydrogen sulfide, characterized by the Henry's Law constant, in MEA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…Further, bmim[doc] predicted data were compared to those of bmim[BF 4 ] and bmim[acetate]. As suggested in the literature [ 38 , 39 , 40 ], the anion change has a more pronounced effect on gases solubility. The variation in Henry’s law constants when replacing [doc] anion by [BF 4 ] and [acetate] anions are larger.…”
Section: Resultsmentioning
confidence: 99%
“…Further, bmim[doc] predicted data were compared to those of bmim[BF 4 ] and bmim[acetate]. As suggested in the literature [ 38 , 39 , 40 ], the anion change has a more pronounced effect on gases solubility. The variation in Henry’s law constants when replacing [doc] anion by [BF 4 ] and [acetate] anions are larger.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the CO 2 and H 2 S mass solubilities do not change appreciably by varying the IL concentration. Additionally, Akhmetshina and coworkers (2017) [118] studied the absorption of H 2 S and CO 2 by 2-hydroxyethylammonium (MEA) or triethanolammonium cations and residues of 2-hydroxy-5-sulfobenzoic acid or pyridine-3-carboxylic acid at various temperatures and partial gases pressures. Results prove that absorbents based on the 2-hydroxyethylammonium cation performed high absorption properties toward the H 2 S. The results of thermal desorption analysis demonstrate that the capture of acid gases in MEA-based absorbents occurred at two stages: through the dissolution in MEA component and in protic ionic liquid.…”
Section: Co 2 Capturementioning
confidence: 99%
“…The idea of mixing ionic liquids with amine solutions provides relatively lower cost and lower partial pressures compared with the conventional acid gas removal process using amine solutions [30]. The mixture of [bmim][Br] and MDEA creates functionalized ionic liquids with a free tertiary amine group tethered on the cations of the ionic liquids.…”
Section: Gas Absorption In Mixture Of [Bmim][br] Ionic Liquid and Mdeamentioning
confidence: 99%